2001
DOI: 10.1046/j.1365-3016.2001.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic disparities in preterm birth: causal pathways and mechanisms

Abstract: SummaryPreterm birth is the leading cause of infant mortality in industrialised societies. Its incidence is greatly increased among the socially disadvantaged, but the reasons for this excess are unclear and have been relatively unexplored. We hypothesise two distinct sets of causal pathways and mechanisms that may explain social disparities in preterm birth. The first set involves chronic and acute psychosocial stressors, psychological distress caused by those stressors, increased secretion of placental corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
224
2
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(245 citation statements)
references
References 184 publications
(266 reference statements)
14
224
2
5
Order By: Relevance
“…In addition, black mothers have been shown to be at increased risk of recurrent preterm delivery and to receive different prenatal care. 13,14 These differences include decreased use of tocolysis, as compared to white mothers, consistent with the observed decrease in tocolysis in the present cohort from the second epoch. 15 In addition, the perinatal mortality rate in black infants is dramatically higher than in white infants even when controlling for early access to prenatal care, demographic characteristics, and pregnancy complications.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, black mothers have been shown to be at increased risk of recurrent preterm delivery and to receive different prenatal care. 13,14 These differences include decreased use of tocolysis, as compared to white mothers, consistent with the observed decrease in tocolysis in the present cohort from the second epoch. 15 In addition, the perinatal mortality rate in black infants is dramatically higher than in white infants even when controlling for early access to prenatal care, demographic characteristics, and pregnancy complications.…”
Section: Discussionsupporting
confidence: 83%
“…25,29,51,65 Thus, countries with high prevalence of risk factors (such as low maternal body mass index and malaria) with a resulting high prevalence of term LBW are also more likely to present high rates of preterm LBW births. In addition, a number of studies 7,23,28,45,50 show that preterm births are more frequent among poor populations. For these reasons, the current fi ndings are more biologically and epidemiologically plausible than those from earlier studies based on data collected pre-1990, which showed little variation of preterm rates across a wide range of LBW prevalences.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal education is one aspect of socioeconomic status that most consistently predicts poor birth outcomes [1]. Other maternal demographic, social and health-related factors have been associated with these adverse birth outcomes, such as single marital status [2], smoking [3][4][5][6][7][8][9][10][11], diabetes [12][13][14] and low social capital [15]. For example, we recently showed that women from Turkey, Iran, Asia, and Latin…”
Section: Introductionmentioning
confidence: 99%